NILAI-NILAI ETIKA KOMUNIKASI MENURUT AL-QUR’AN DAN MENJAGA KOMUNIKASI ANTAR MANUSIA MENURUT AL-QUR’AN - Muhammad Nurul Fadillah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this study is to understand communication with ethical values according to the Qur'an, so that in this study using qualitative research methods with literature study sources, the results of this research in communication activities must be mutual respect and respect for differences, both differences in ethnicity, race and culture, as well as differences in choices, and opinions. This is as affirmed by the word of Allah Almighty in the Qur'an surah al-Hujurat verse 3 which means ―O man, Verily We created you from a man and a woman and made you into nations and tribes so that you might know each other. Indeed, the noblest among you in the sight of Allah is the most pious among you. Indeed, Allah is All-Knowing, All-Knowing.